Sawflies out of Gondwana: phylogenetics and biogeography of Argidae (Hymenoptera). (5th November 2021) - Malagón‐Aldana, Leonardo A.; Jensen, Arn R.; Smith, David R.; Shinohara, Akihiko; Vilhelmsen, Lars
ABSTRACT: We present the first phylogenetic hypothesis for the cosmopolitan family Argidae based on both molecular and morphological data. Furthermore, we present a biogeographic scenario based on a dated phylogeny and interpret the evolutionary history of the family. Information from sequences of eight genes is analysed to reconstruct the phylogeny of the Argidae based on maximum likelihood and Bayesian inference. Total evidence Bayesian analyses are also conducted, combining the molecular dataset with data from adult and larval morphology. For the historical biogeographic reconstruction, divergence times are estimated using node dating with uncorrelated relaxed‐clock analysis, and ancestral biogeographical distributions are estimated applying a Dispersal Extinction Cladogenesis model and a Bayesian binary model. Argidae s.s. is retrieved as monophyletic in all analyses and the clade Zenargidae + (Argidae + Pergidae) is better supported when combining molecular and morphological characters, and when excluding the saturated third codon position in the molecular analysis. Within Argidae, two large clades corresponding to the subfamilies Arginae and Sterictiphorinae sensu Benson are retrieved as monophyletic. The ancestral distribution of Arginae and Sterictiphorinae is estimated to be the Australian and Neotropical regions. Divergence of Argidae‐Pergidae and Arginae‐Sterictiphorinae is estimated to occur in the middle‐upper Jurassic before or during the east‐west Gondwana breakup. Diversification of Argidae may be associated with the radiation of angiosperms in the Early Cretaceous, especially for the Neotropical Sterictiphorinae after the separation of South America and Africa. Arginae were probably introduced to the northern hemisphere by dispersal to Africa and/or India and subsequent continental collision with Eurasia in the Cenozoic. The occurrence of Sterictiphorinae in the northern hemisphere is more difficult to explain. Maternal care and brood guarding behaviour evolved independently in Argidae and Pergidae, with a single origin in a subclade (Dielocerini) of Sterictiphorinae. Abstract : Argidae s.s. is retrieved as monophyletic. The clade Zenargidae + (Argidae +Pergidae) is retrieved when combining molecular and morphological characters and when excluding the saturated third codon position. Divergence of families Argidae‐Pergidae and the subfamilies Arginae‐Sterictiphorinae is estimated to occur in the middle‐upper Jurassic before or during the east‐west Gondwana breakup. Introduction to the northern hemisphere for Arginae probably occurred by dispersal to Africa and/or India and subsequent collision with Eurasia in the Cenozoic. For Sterictiphorinae, no plausible hypothesis was supported.